2014
DOI: 10.1111/gcb.12729
|View full text |Cite
|
Sign up to set email alerts
|

The capacity to cope with climate warming declines from temperate to tropical latitudes in two widely distributed Eucalyptus species

Abstract: As rapid climate warming creates a mismatch between forest trees and their home environment, the ability of trees to cope with warming depends on their capacity to physiologically adjust to higher temperatures. In widespread species, individual trees in cooler home climates are hypothesized to more successfully acclimate to warming than their counterparts in warmer climates that may approach thermal limits. We tested this prediction with a climate-shift experiment in widely distributed Eucalyptus tereticornis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(143 citation statements)
references
References 100 publications
8
124
1
2
Order By: Relevance
“…This may have been caused by having a relatively small number of climates of origin or a limited geographic range. For the widespread species Eucalyptus grandis W.Hill and Eucalyptus tereticornis Sm., intraspecific variation in A and growth showed that the capacity to cope with 3.5 C warming is higher in cooler sites, suggesting that trees from warmer sites are near a thermal limit (Drake et al 2015). Our results for photosynthetic tolerance of a springtime heatwave are somewhat similar for plants in aCO 2 but not eCO 2 .…”
Section: Photosynthesis and Climate Of Originsupporting
confidence: 54%
See 3 more Smart Citations
“…This may have been caused by having a relatively small number of climates of origin or a limited geographic range. For the widespread species Eucalyptus grandis W.Hill and Eucalyptus tereticornis Sm., intraspecific variation in A and growth showed that the capacity to cope with 3.5 C warming is higher in cooler sites, suggesting that trees from warmer sites are near a thermal limit (Drake et al 2015). Our results for photosynthetic tolerance of a springtime heatwave are somewhat similar for plants in aCO 2 but not eCO 2 .…”
Section: Photosynthesis and Climate Of Originsupporting
confidence: 54%
“…suggest that their distributions are related to tolerance of thermal extremes, rather than their growth rate responses to typical sublethal conditions (Paton 1980). These prior results show that responses to both episodic temperature extremes and conditions that mimic slow, chronic warming are important for photosynthetic physiology of some Eucalyptus species, and can help explain their geographic distribution (Drake et al 2015). Previous research has observed genotypic variation in physiological response to eCO 2 within E, camaldulensis var.…”
Section: Variation In Heat Stress Tolerancementioning
confidence: 71%
See 2 more Smart Citations
“…Evidence exists to show that many Eucalyptus can grow successfully outside their natural distributions at warmer mean annual temperatures (Butt et al, 2013;Booth, 2015;Booth et al, 2015) and are highly plastic in traits related to maintaining fitness under novel conditions (Byrne et al, 2013;McLean et al, 2014). Adult plants may have the capacity to buffer extremes of climate through physiological resistance or phenotypic plasticity (for example, changes in water use efficiency and specific leaf area) (Nicotra et al, 2010;Drake et al, 2014) but it is thought that long-lived tree species are unlikely to track rapidly changing environments effectively due to slow response times to changing climates (Pearson and Dawson 2003;Butt et al, 2013). The reproductive stages of a plant's life cycle often represent a major bottleneck for species persistence, and tolerance in this early developmental stage is critical for survival, more so than at the adult stage (Watkinson, 1997;Lloret et al, 2004).…”
Section: Introductionmentioning
confidence: 99%